2022
DOI: 10.3389/fimmu.2022.943325
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic shotgun sequencing and metabolomic profiling identify specific human gut microbiota associated with diabetic retinopathy in patients with type 2 diabetes

Abstract: BackgroundDiabetic retinopathy (DR) is a common microvascular complication of diabetes mellitus (DM) and is one of the leading causes of blindness among DM patients. However, the molecular mechanism involving DR remains unclear.MethodsA case–control study with age-, sex-, and duration-matched diabetic patients and controls was conducted, which included 15 type 2 DM (T2DM) patients with DR and 15 T2DM patients without DR. Shotgun sequencing and non-targeted metabolomic profiling analyses of fecal samples were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 48 publications
1
19
1
1
Order By: Relevance
“…Shotgun metagenomic (SM) data enable high resolution in estimation of taxon abundance from phylum (Sunagawa et al, 2013 ), to strain level (Scholz et al, 2016 ) within the original sample. In addition to taxonomic profiling, shotgun sequencing data is used for studying the functional potential of the human microbiome (Li et al, 2022 ). In the analysis of SM data, the sequencing depth serves as a crucial factor for understanding how it might affect the results.…”
Section: Exploring the Diversity Of Microbiome Data Types And Challen...mentioning
confidence: 99%
“…Shotgun metagenomic (SM) data enable high resolution in estimation of taxon abundance from phylum (Sunagawa et al, 2013 ), to strain level (Scholz et al, 2016 ) within the original sample. In addition to taxonomic profiling, shotgun sequencing data is used for studying the functional potential of the human microbiome (Li et al, 2022 ). In the analysis of SM data, the sequencing depth serves as a crucial factor for understanding how it might affect the results.…”
Section: Exploring the Diversity Of Microbiome Data Types And Challen...mentioning
confidence: 99%
“…Recently, a cross-sectional study carried out in Japanese individuals has shown that the composition and functional profiles for GM in T2D patients were significantly different from those in the healthy group [ 74 ]. Moreover, the habitual dietary intake, especially sucrose intake, was more strongly associated with these differences, suggesting that reducing sucrose intake might help prevent the onset of T2D through prevention of gut dysbiosis [ 75 ].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…In addition, at the genus level, Bifidobacterium and Lactobacillus decreased in faecal samples. Cellular, environmental and metabolism-related pathways were found to be at higher levels in the GM in T2D-DR patients [ 74 ].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Metode shotgun metagenomik telah digunakan untuk analisis diversitas metabolisme (L. Li et al, 2022;Sarah R Carrino-Kyke et al, 2013), investigasi outbreak patogen, deteksi biomarker (Anders B Dohlman et al, 2022), dan analisis mikrobiom usus (Salamon et al, 2021). Alur kerja analisis metagenomik shotgun secara umum ditampilkan pada gambar 3.…”
Section: Wawasan Bioinformatika Next Generation Sequencing Dalam Samp...unclassified